The Impact of the COVID-19 epidemic on Fintech - Kong, Yingru; Wu, Jun (Transactions on Economics, Business and Management Research, 2023)
Fintech is a mainstream trend in digital transformation and it is an important strategic goal adopted by countries to help the real economy. The sudden COVID-19 epidemic has a significant impact on the global economy and pushes the development of Fintech to a new stage. This paper tries to explore the impact of the COVID-19 epidemic on Fintech innovation and regulation by collecting relevant literature from China Knowledge Network and Web of Science, and applying bibliometric methods such as literature quantity statistics and keyword mutation. The study found that: 1) after the outbreak of the COVID-19 epidemic, the number of literatures related to financial technology has increased significantly, and Fintech has become a research hotspot for scholars; 2) from the perspective of the research body, scholars have shifted their interpretations of the connotation of Fintech from conceptual analysis to practical exploration; 3) from the perspective of research content, the COVID-19 epidemic has promoted the technological innovation and application of Fintech, and the results of this field of research have been more fruitful. However, the economic downturn crisis brought by the COVID-19 epidemic has forced regulators to adopt loose regulatory policies, which led to a decline in scholars’ attention to financial technology regulation for the regulation of financial technology and a slight lack of research enthusiasm. In the future, sustained efforts should be made to pay attention to the research on Fintech regulation, strengthen the connection between macro and micro perspectives of the discipline, and develop a personalized development path for Fintech.